Evaluation of PFWD as potential quality control tool of pavement layers - Kavussi, Amir; Yasrobi, Shahaboddin (Journal of Civil Engineering and Management, 2010)
Portable Falling Weight Deflectometer (PFWD) that can be considered as simple equipment is mainly used to measure elastic moduli of pavement unbound layers. This paper evaluates the potential use of PFWD to reliably measure the elastic modulus of pavement layers. To achieve this, PFWD tests were conducted on highway sections selected from different projects in Tehran. The California Bearing Ratio (CBR) laboratory tests were also conducted on samples collected during field tests. PFWD testing parameters were varied while performing the field testing. These included drop weight, drop height, plate diameter and position of additional geophones. In addition, PFWD moduli were compared with those obtained from performing FWD testing on the same site. It was found that drop mass and loading plate size affect PFWD modulus significantly. In addition, the results indicated that good correlation exist between PFWD moduli and FWD and CBR results. Published Published Online: 24 Jun 2011